Modelling and simulation-based analysis of a façade-integrated decentralized ventilation unit. (May 2020) - Bonato, P.; D'Antoni, M.; Fedrizzi, R.
Abstract: This article presents a performance study of a façade-integrated decentralized mechanical ventilation unit and aims to assess the potential of this solution to reduce the HVAC energy consumption in perimetral office areas. The energy savings are estimated for three representative European climates by performing numerical simulations with the TRNSYS software. The numerical models of the aeraulic components are calibrated by means of laboratory tests conducted on a real-scale prototype of ventilation unit. Based on the analysed climate and building, it is found that the studied solution can effectively reduce the energy consumption of perimetral office spaces and that large electricity savings (up to 65%) can be achieved with respect to CAV centralized systems. This is mostly connected to a lower electricity consumption of the fans and, at a lower extent, to the use of mechanical ventilative cooling strategies and Demand Control Ventilation (DCV) strategies. Thanks to better ventilation strategies, a reduction of the cooling demand between 35% and 70% is attained for the three reference locations. Highlights: The design of a novel façade-integrated ventilation unit for offices is presented. The numerical models of the ventilation unit and the adjacent space are described. The energy performances of the solution are assessed via numerical simulation.